Alternative approaches beyond budgeting for indigenous communities - Sumantri, Joko; Zunaidi, Achmad; Panjaitan, Rido Parulian; Trisulo, Trisulo (Educoretax, 2025)
Beyond Budgeting has emerged as a promising model in the modern context where adaptive and sustainable fund management is critically needed. This approach empowers organizations to achieve greater flexibility, innovation, and enhanced performance. This study examines the potential implementation of a Beyond Budgeting framework in managing village funds within the Baduy community in Indonesia. The research employed a descriptive-qualitative methodology, conducted in Kanekes, Lebak Regency. A qualitative approach was chosen to gain an in-depth understanding of participants' perspectives and experiences, utilizing semi-structured interviews, direct interactions, and observation. Data were analyzed to identify patterns and key findings relevant to village fund management. The observation analysis included data grouping, comparative analysis of similarities and differences in observed events, and interpretation within the local context. The findings suggest that integrating Beyond Budgeting principles into the Baduy community's village fund management is both feasible and highly relevant. The Baduy tribe exhibits strong local wisdom in resource and environmental management, emphasizing sustainability and communal values. Crucially, the principles of flexibility, transparency, and participation embedded in the Beyond Budgeting model align closely with these traditional values. Therefore, adapting Beyond Budgeting in the Baduy context could significantly enhance fund management practices while simultaneously preserving cultural integrity and promoting sustainable development.